An examination of the interactions between museum educators and students on a school visit to science museum. Issue 2 (29th September 2018) - Shaby, Neta; Ben‐Zvi Assaraf, Orit; Tal, Tali
Abstract: Today, science is a major part of western culture. Discussions about the need for members of the public to access and understand scientific information are therefore well established, citing the importance of such information to responsible citizenship, democracy, socially accountable scientific research and public funding (National Research Council [2009] Learning science in informal environments: People, places, and pursuits . National Academies Press). In recent years there has been an increased interest in investigating not just what visitors to informal environments have learnt after a visit, but also how visitors interact and engage with exhibits during the visit (Davidsson & Jakobsson [2012] Understanding interactions at science centers and museums: Approaching sociocultural perspectives. Rotterdam: Sense Publishers). Within the field of school visits to science museums, however, interactions between students and museum educators (MEs) remain relatively unexplored. In our study of such school visits, we are mainly interested in the interactions that take place between three agents—the students, the museum educator and the physical setting of the exhibit. Using moment‐to‐moment fine grain analysis of multiple interactions allowed us to identify recurring patterns between students and the museum educators around exhibits, and to examine the MEs' mediational role during the interactions, and the practices they employ to engage students with exhibits. Our study revealed that most interactions between MEs and students consist of technical explanations of how to operate the exhibits. The interactions that do move past this stage often include two main practices, which the MEs use to promote students' engagement with the exhibits: physical instruction and engaging the students emotionally. Understanding what is actually happening in the learning process that occurs during students' interactions with exhibits can help museum educators and exhibit designers improve the experiences of students on school visits.